(untitled) (Journal of the College of Basic Education, 2023)
The research dealt with the phenomenon of grammatical inconsistency in the book Questions of the Glorious Qur’an and Their Answers by Zain al-Din al-Razi (d. 666 AH). To show the magnificence and flexibility of this system, and to add a new significance